Ideologies of the Raj - Metcalf, Thomas R., 1934- (Cambridge ; New York ; New Delhi : Cambridge University Press, 1995)
Students of modern Indian history and the British Empire will find this book relevant & accessible. It examines how the British sought to justify their rule over India.
Includes bibliographical references (p. 235-240) and index.
RS
In English.
Keywords: India -- History -- British occupation, 1765-1947.